SOCIALIZATION OF THE DANGERS AND EFFECTS OF DRUG AND PSYCHOTROPIC USE FOR THE PROGRESS OF THE NATION (STOP DRUGS) - dianti, Mely Purna; Prodyanatasari, Arshy; Sumaningrum, Ningsih Dewi; Agustina, Novia; Putri, Mardiana Prasyani; Dewi, Yoanita Indra Kumala (Universitas Bakti Tunas Husada, 2024)
The service team carried out a community service program because the juvenile drug problem was already very worrying. The community really hopes that schools can prevent the harm and spread of drugs. However, there are several problems faced by the partner school, SMPN 1 Kras, including: the teacher council lacks the capacity and understanding of drug problems and dangers; lack of training and media socialization and education about the dangers of drugs; and lack of media development and socialization and education facilities about the dangers of drugs in partner schools. Departing from these problems, the service team provides solutions through community service activities, namely: a) Providing education to adolescents about: Dangers of Drugs and How to Avoid Drugs through training and seminars on the dangers of drugs, b) Improving the ability of adolescents to develop media used for socialization of the dangers of drugs. This service activity will be carried out for three days through training and socialization methods or methods. The results of the activity are known that there is an increase in understanding of various types of drugs, the impact on adolescents, and how to prevent them, Increasing the ability of adolescents, BK teachers, and homeroom teachers in making socialization and education media on the dangers of drugs using or utilizing social media, Building synergy of cooperation between partners and the service team of the BK study program of SMPN 1 KRAS in preventing the dangers of drugs for students at SMPN 1 KRAS in particular and the revitalization of the existence and role of PIK R in SMPN 1 KRAS to educate teenagers about the dangers of drugs.Keywords: NAPZA; Socialization; Adolescent.